PSYCHOLOGICAL - PEDAGOGICAL AND ORGANIZATIONAL CONDITIONS OF INCLUSIVE EDUCATION - Omonova Shakar Jumanazar qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discusses the history of the development of education for children with disabilities, its importance, the role of inclusion in preparing children with disabilities for social life, and an analysis of the results of a small research study conducted among university students.